2017
DOI: 10.1161/circulationaha.117.028201
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Autonomous Aldosteronism

Abstract: Background Both aging and inappropriate secretion of aldosterone increase the risk for developing cardiovascular disease; however, the influence of aging on aldosterone secretion and physiology is not well understood. Methods The relationship between age and adrenal aldosterone synthase (CYP11B2) expression was evaluated in 127 normal adrenals from deceased kidney donors (age 9mo-68y). Following immunohistochemistry, CYP11B2 expressing area and areas of abnormal foci of CYP11B2 expressing cells, called aldos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
119
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(133 citation statements)
references
References 35 publications
11
119
1
2
Order By: Relevance
“…APCCs are histopathological findings of large clusters of CYP11B2 (also known as aldosterone synthase) expression that invade the zona fasciculata, harbor pathogenic mutations known to increase aldosterone secretion, and are not suppressed in the face of volume expansion or aldosterone excess(15, 16). Importantly, APCCs have been found in >50% of morphologically normal adrenal glands (with no apparent tumor or hyperplasia) and increase in prevalence with older age(18); consistent with our findings that autonomous aldosterone secretion may be a common pathogenic contributor to incident hypertension.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…APCCs are histopathological findings of large clusters of CYP11B2 (also known as aldosterone synthase) expression that invade the zona fasciculata, harbor pathogenic mutations known to increase aldosterone secretion, and are not suppressed in the face of volume expansion or aldosterone excess(15, 16). Importantly, APCCs have been found in >50% of morphologically normal adrenal glands (with no apparent tumor or hyperplasia) and increase in prevalence with older age(18); consistent with our findings that autonomous aldosterone secretion may be a common pathogenic contributor to incident hypertension.…”
Section: Discussionsupporting
confidence: 91%
“…When compared to participants with higher renin activity, participants with a suppressed renin phenotype were older, more enriched with women and African-Americans, and had higher systolic blood pressure. Notably, although these participants had the lowest serum aldosterone concentrations, they had markedly elevated aldosterone-to-renin ratios (ARR>750 pmol/L per μg/L/h, or >30 ng/dL per ng/mL/h in conventional units), since they also had the lowest PRA(18) (Table 1). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical correlates indicated that APCCs number and size increase with age, (69) paralleled by a progressive transition towards a discontinuous CYP11B2 expression pattern in older-age adrenal glands which might account for the age-related changes in renin and aldosterone physiology (70).…”
Section: Somatic Mutations In Aldosterone Producing Cell Clustersmentioning
confidence: 99%
“…Among blacks in the Jackson Heart Study,6 aldosterone was positively associated with insulin resistance, while higher levels of aldosterone across the spectrum were associated with a dose‐dependent higher risk of the development of type 2 diabetes mellitus over 8 years. Recent observations demonstrate that aldosterone can be produced autonomously from aldosterone producing cell clusters within morphologically normal adrenal glands with a large spectrum and high prevalence of subclinical aldosteronism 7, 8, 9. Thus, we examined the association of aldosterone and PRA with glucose metabolism and incident diabetes mellitus across the spectrum of aldosterone levels in a multiethnic cohort to determine if there are racial/ethnic differences.…”
Section: Introductionmentioning
confidence: 99%